Freire's Praxis, Democracy and Critical Consciousness in Islamic Education - Fauzi, Muhamad Restu; Usman, Usman (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
Critical philosophy in education assumes that students are so naive and unable to read social reality critically, and this also happens in Islamic education. Paulo Freire tries to promote the importance of student-centred education, active participation and critical consciousness in education. This study aims to: (1) explore Freire's ideas about praxis; (2) explore Freire's thoughts on democracy; (3) explore Freire's thinking about critical consciousness; (4) integrate the concepts of praxis, democracy and critical consciousness in Islamic education. This is literature research which involves review of literature that is relevant to Freire's concepts and their application in Islamic education. The findings of this study are: (1) Praxis allows students to link Islamic knowledge and values with concrete actions in life; (2) Democracy promotes student participation in decision-making and open dialogue, enabling them to actively contribute to learning; (3) Critical consciousness helps students understand the structure of society and analyze their understanding of Islamic teachings critically; (4) The concepts of praxis, democracy and critical consciousness in Islamic education provides opportunities for students to integrate religious teachings with their life experiences, understand the social context and develop a critical understanding of Islam.